Dual utilization of CO2 in polymethyl methacrylate: A predictive solubility model for microcellular foaming and controlled drug release - Lim, Donghwan; Kim, Jaehoo; Kwon, Jiwon; Kim, Kwanhoon; Kim, Jaewoo; Jang, Yong Hoon; Yoon, Jun Young; Cha, Sung Woon (Elsevier BV, 2026)
This study propose and validate a testing methodology for process control of the Microcellular Foaming Process (MCP), which is essential for achieving reproducible and uniform cell morphologies. A critical component of this methodology is the accurate prediction of CO2 solubility. Previous studies have mainly relied on the Sanchez–Lacombe and Peng–Robinson–Stryjek–Vera equations (PRSV–EOS) of state along with the chemical potential equilibrium approach. However, PRSV–EOS exhibit limited accuracy in predicting CO2 density near the critical points and phase transition boundaries. To improve the accuracy of such predictions, herein, we used the Span–Wagner equation of state. Although a constant binary interaction parameter was used for computational simplicity, the model was successfully validated with an average relative deviation below 8.5 % in the range of 263–313 K and 0–8 MPa. Based on the calculated solubility, post-analysis of the MCP results enabled the identification of essential parameters for predicting cell density under these conditions. Additionally, a polymethyl methacrylate–sodium benzoate (NaBz) composite was fabricated and tested for its release characteristics The findings revealed that the release characteristics varied with the NaBz volume fraction of this composite and the initial porosity generated by the MCP, showing percolation-dependent behavior. This confirms the MCP's potential as a valuable testing and fabrication technique for high-value biomedical applications.